2018
DOI: 10.1029/2018wr022816
|View full text |Cite
|
Sign up to set email alerts
|

Climate Elasticity of Low Flows in the Maritime Western U.S. Mountains

Abstract: Summer streamflow is an important water resource during the dry summers in the western United States, but the sensitivity of summer minimum streamflow (low flow) to antecedent winter precipitation as compared with summer evaporative demand has not been quantified for the region. We estimate climatic elasticity of low flow (percent change in low flow divided by percent change in climatic forcing variable) with respect to annual maximum snow water equivalent (ESWE), winter precipitation (EPPT), and summer potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 81 publications
(172 reference statements)
7
45
0
1
Order By: Relevance
“…Our results show that shifts in precipitation-runoff relationship may take place both in volcanic, subsurface-flow-dominated and in transitional-to-granitic, surface-runoff-dominated basins. This may seem counterintuitive as the volcanic Almanor sub-basin has a relatively small inter-annual variability in low flows that agrees with other studies in similar contexts (Jefferson et al, 2008;Tague et al, 2008;Cooper et al, 2018), and this variability is an important driver of shifts in Australian basins (Saft et al, 2016b). However, while the surface-runoff-dominated East Branch does return larger shifts both overall (M Q ) and for individual droughts (m Q , see Section 3.2), both this sub-basin and the Almanor are rain-shadowed (aridity index of ∼1.5 and 1.1, respectively).…”
Section: Why Et Is Misrepresented During Droughts: Climate Elasticitysupporting
confidence: 88%
See 2 more Smart Citations
“…Our results show that shifts in precipitation-runoff relationship may take place both in volcanic, subsurface-flow-dominated and in transitional-to-granitic, surface-runoff-dominated basins. This may seem counterintuitive as the volcanic Almanor sub-basin has a relatively small inter-annual variability in low flows that agrees with other studies in similar contexts (Jefferson et al, 2008;Tague et al, 2008;Cooper et al, 2018), and this variability is an important driver of shifts in Australian basins (Saft et al, 2016b). However, while the surface-runoff-dominated East Branch does return larger shifts both overall (M Q ) and for individual droughts (m Q , see Section 3.2), both this sub-basin and the Almanor are rain-shadowed (aridity index of ∼1.5 and 1.1, respectively).…”
Section: Why Et Is Misrepresented During Droughts: Climate Elasticitysupporting
confidence: 88%
“…Also, the model systematically underestimated both the absolute value and the interannual variability of changes in sub-surface storage, in particular for the Almanor sub-basin ( Figure S3) and for the Feather River at Oroville ( Figure 7); PRMS failed to reproduce the multi-decadal decline in storage observed in all (sub-)basins as a result. While the observed changes in sub-surface storage used in this paper to evaluate PRMS may suffer from unquantifiable uncertainty across precipitation, full-natural flow, and GAM-estimated evapotranspiration, this decline was confirmed by other soft data collected on the river (Freeman, 2011) and agrees with a general trend of declining summer low flows in the Maritime Western U.S. (Cooper et al, 2018).…”
Section: The Observed Vs Modeled Water Balancesupporting
confidence: 68%
See 1 more Smart Citation
“…We attribute the lower RE in 2015 to a combination of (a) increased contribution to the depleted aquifer storage from the previous few years of drought, and (b) increased ET during an extended snow‐free season. This assessment is consistent with the findings of Berghuijs et al (2014), Cooper et al (2018), and Godsey et al (2014), who showed that increases in rainfall precipitation proportions across historically snow‐dominated basins resulted in lower runoff amounts.…”
Section: Resultssupporting
confidence: 91%
“…The sensitivity to both P and PET increases with increasing n value since the higher value of n generally corresponds to greater E for a given P and PET (Figure 2). The n value is a function of precipitation, topography, and slope [47,65,72,73], indicating lower water availability in regions with higher n value.…”
Section: Historic Climate Water Balance Components and Streamflow Smentioning
confidence: 99%